(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article reviews Uzbekistan-specific challenges, drawing on local studies (e.g., Fozilova, 2026; Madraximova, 2026) and comparative evidence from non-Anglophone contexts. It proposes targeted mechanisms grounded in Dörnyei’s L2 Motivational Self System and Self-Determination Theory: mandatory early-year EMP integration aligned with clinical subjects and national reforms, peer-assisted learning (PAL) in mixed local-international groups, blended learning via platforms like Moodle/HEMIS with gamification and role-playing simulations, and institutional support including specialized teacher training and language centers. These strategies aim to enhance instrumentality (career benefits), strengthen the Ideal L2 Self (vision as a globally competitive doctor), reduce anxiety, and promote sustainable engagement amid Uzbekistan’s drive for international medical education competitiveness.